Association between lean body mass to visceral fat mass ratio and bone mineral density in United States population: a cross-sectional study - Longti Li; Huiqin Zhong; Ya Shao; Xu Zhou; Yu Hua; Maoqian Chen (BMC, 2023)
Abstract Background Studies have explored the correlation between body composition and bone mineral density (BMD), but there has yet to be a consensus. Thus, the present study aims to comprehensively investigate the association between lean body mass, adipose tissue, and BMD. Methods We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) (2011-2018) with 11,227 subjects. Multiple linear regression, smoothed curve fitting, threshold, and saturation effect analysis were used to explore the association between lean body mass, visceral fat mass, and BMD. Also, we used the lean body mass to visceral fat mass ratio (Log LM/VFM) as a proxy variable to analyze its association with BMD alone. Results After adjusting for potential confounding factors, the results showed a positive correlation between lean mass and total BMD (for continuous: β = 0.078, P < 0.001; for quartile: β = 0.138, P < 0.001), while visceral fat mass was negatively correlated (for continuous: β = -0.027, P < 0.001; for quartile: β = -0.065, P < 0.001). A positive correlation was observed when the alternative variable Log LM/VFM was analyzed separately for its association with BMD (for continuous: β = 0.034, P < 0.001; for quartile: β = 0.084, P < 0.001). In addition, subgroup analyses for gender, age, body mass index, hypertension, and diabetes showed that all subgroups except the diabetes subgroup showed a substantial degree of robustness (P < 0.05). The smoothed curve fitting showed a nonlinear relationship between Log LM/VFM and BMD, and there was a threshold effect with a critical value of 2.60. Conclusion Maintaining a proper ratio of lean body mass and visceral fat mass is beneficial for increasing BMD.